Interrelationships Among Men's Threat Potential, Facial Dominance, and Vocal Dominance. (7th March 2017) - Han, Chengyang; Kandrik, Michal; Hahn, Amanda C.; Fisher, Claire I.; Feinberg, David R.; Holzleitner, Iris J.; DeBruine, Lisa M.; Jones, Benedict C.
The benefits of minimizing the costs of engaging in violent conflict are thought to have shaped adaptations for the rapid assessment of others' capacity to inflict physical harm. Although studies have suggested that men's faces and voices both contain information about their threat potential, one recent study suggested that men's faces are a more valid cue of their threat potential than their voices are. Consequently, the current study investigated the interrelationships among a composite measure of men's actual threat potential (derived from the measures of their upper-body strength, height, and weight) and composite measures of these men's perceived facial and vocal threat potential (derived from dominance, strength, and weight ratings of their faces and voices, respectively). Although men's perceived facial and vocal threat potential were positively correlated, men's actual threat potential was related to their perceived facial, but not vocal, threat potential. These results present new evidence that men's faces may be a more valid cue of these aspects of threat potential than their voices are.